Role and Activities of the GGOS Bureau of Products and Standards - Angermann, D. (2025)
The Bureau of Products and Standards (BPS) is a key component of the Global Geodetic Observing System (GGOS) of the International Association of Geodesy (IAG). It supports GGOS in its goal to provide consistent geodetic products needed to monitor, map, and understand changes in the Earth’s shape, rotation, and gravity field. A major objective of the BPS is to keep track and foster homogenization of adopted geodetic standards and conventions as a fundamental basis for the generation of consistent geodetic products, such as the celestial reference frame, the terrestrial reference frame, Earth Orientation Parameters, satellite orbits, gravity field models and heights. This requires a close collaboration across all IAG components, as well as with other bodies dealing with standards and conventions, such as the IAU Commission A3 ’’Fundamental Standards”, the International Organization for Standardization (ISO) and the Committee on Data for Science and Technology (CODATA). This contribution presents the role of the BPS and it highlights some of the recent activities. A key issue is the regular update of the BPS inventory of standards and conventions used for the generation of geodetic products to incorporate the latest developments in the field. Further activities focus on the description and promotion of geodetic products to make other disciplines and society aware of geodesy and its beneficial products, and on the definition of Essential Geodetic Variables (EGVs).